Assessment of Ring Seine Fishery Performance with a 25-HP OBM along the Mangaluru Coast - Naik, Jaya; Atnur, V. S.; Dharshan, K. S.; Varadaraju, S.; Badami, S. H. (International Journal of Bio-resource and Stress Management, 2026)
To know the catch composition of the Ring seine operated at a depth of 15 m and 20 m along the Thanirbhavi coast off Mangaluru during the month of August-2023 to December-2024. Ring Seine was used to operate along the Mangaluru coast off Karnataka. The Experiment was started during the year 2023–2024 with Out Board Motor (OBM) Engine fitted with FRP canoe of Over All Length (OAL) of 13.8 m. The study was carried out at two depths Viz. 15 m and 20 m. The experiment was carried out once in fortnight for each months. The catch found was 1,648.40 kg in case of 15 m depth. At 20 m depth the catch was 16,786kg. The major species caught was Sardine and Mackerel. The fishes were segregated and sorted out species wise and size wise and later it was brought to the stored shore under the hatches with a chilled sea water to maintain the fresh quality until it goes for auctioning. This Ring seine fishing operation was carried at both the depths and the Predominant catch found at the depth of 20 m. This Ring seine operations was carried out to know the exact depth of operation for the 13.8m OBM engine and the commercially available species, which could help the fisher community to earn even in the fishing ban in the Karnataka coast. This Ring seine played a vital role in catching the pelagic fishes especially Sardine and Mackerel.